The Manufacture Method of Potato Dextrose Agar (PDA) as Growth Media for Airborne Mold in the Science Laboratory of SMAS Pesantren IMMIM Makassar - Kaswi, Nurwilda; Wahyuni, Sri; Annisa, Riska; Al Adawiah, Putri Rabiah; A. Salim, Indra Permata (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract The laboratory is the main learning place apart from the classroom. Some of the places that have the highest levels of indoor air contamination, one of them is the laboratory which can be contaminated by pathogenic microorganisms including mold. This group of fungi-like mold has mycotoxins that can cause a variety of adverse health effects and pose a serious health threat when immunity decreases. There are several factors that influence the growth of mold in the laboratory, including temperature and humidity. This service aims to carry out a simple practical work on making a PDA. The method activity used is experimental based with descriptive and qualitative data analysis from practicum results. The practicum was guided directly in the science laboratory at SMAS Pesantren IMMIM Makassar and was attended by 25 students and then the students practiced in groups. Through this activity, it can be concluded that the practicum carried out can be followed by students well so that students can practice how to make PDA media which can be used as a medium for growing airborne molds.